2019
DOI: 10.3906/bot-1901-32
|View full text |Cite
|
Sign up to set email alerts
|

Bioassessing ecological status of surface waters in the Araban-Yavuzeli catchment (Turkey): application of diatom indices

Abstract: Within the scope of the European Union Water Framework Directive, diatom assemblages as biological quality components were used to evaluate the ecological status of 12 surface waters in the Araban-Yavuzeli catchment between October 2013 and October 2014. A total of 75 diatom species were identified during the study period. Amphora ovalis, Denticula elegans, Gomphonema parvulum, Gomphonema truncatum, and Navicula cryptocephala were commonly observed. The relationship between diatom assemblages and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In some studies with rivers from different basins that were monitored using diatom indices, the TIT gave compatible results with environmental parameters and indicator species (Çelekli & Bilgi, 2019;Çelekli, Lekesiz, & Yavuzatmaca, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…In some studies with rivers from different basins that were monitored using diatom indices, the TIT gave compatible results with environmental parameters and indicator species (Çelekli & Bilgi, 2019;Çelekli, Lekesiz, & Yavuzatmaca, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…Pollution‐sensitive species (e.g., A. bryophila , A. minutissimum , E. minutum , and C. excisa showed close relationships with especially D1 and D2 stations of Değirmendere stream (Figure 5), which had TP optima levels lower than the 25th percentile (Figure 7). These species were also found in semi‐arid regions, where they had similar phosphorous optima (Çelekli & Arslanargun, 2019; Çelekli & Bilgi, 2019). These pollution‐sensitive species having TP optima values are higher than those of Austria (Binder, 2001) and are lower than that of Australia (Oeding & Taffs, 2017) due to the effects of different ecoregions on different ecosystems.…”
Section: Discussionmentioning
confidence: 85%
“…Among the European diatom indices, IPS having more diatom species has been commonly used to evaluate the surface waters of the Eastern Mediterranean Region such as Cyprus (Cantonati et al, 2020; Pissaridou et al, 2021) and Greece (Karaouzas et al, 2019). The European indices cannot efficiently adapt to the particular hydrological and climatic conditions of the Eastern Mediterranean Region (Çelekli et al, 2018; Çelekli & Bilgi, 2019; Çelekli & Lekesiz, 2020; Lazaridou et al, 2018) because ecoregional factors influence the trophic weight of diatom taxa. The species list of TIT did not include all of the taxa found in the streams and so the revision of the species list is necessary for better the bioassessment of streams.…”
Section: Discussionmentioning
confidence: 99%
“…Research dealing with bioindicators has gained momentum to understand the responses of species to stressors and such kinds of studies indicate an uptrend. Many bioassessment studies deal with diatom metrics have been carried out in Europe, Asia, and America (e.g., Lavoie et al, 2009;Wachnicka et al, 2011;Bere, 2016;Vilmi et al, 2016;Xue et al, 2019;Szczepocka et al, 2019;Tapolczai et al, 2019;Edwards et al, 2020), while there are a few studies in Turkey, e.g., in the West Mediterranean basin (Çelekli and Lekesiz, 2020), Aras basin (Çelekli et al, 2019a), Sakarya basin (Çetin and Demir, 2019) and the southeast of Anatolia (Çelekli and Arslanargun, 2019;Çelekli and Bilgi, 2019;Çelekli and Kapı, 2019). Results indicated that the number of studies related to diatom indices based on the ecoregion should increase to obtain clearer and more accurate results in Turkey.…”
Section: Rhoicosphenia Abbreviata Ti Tittdilmentioning
confidence: 99%
“…A recently developed diatom index called TIT (Trophic Index Turkey) (Çelekli et al, 2019b) was the first diatom index in Turkey. The suitability of this index has been tested in different geographical and ecological regions of Turkey; for example, the freshwaters of the Western Anatolian basin (Toudjani et al, 2017), the North Aegean basin (Çelekli et al, 2018), Aras river basin (Çelekli et al, 2019a), the West Mediterranean basin (Çelekli and Lekesiz, 2020), and the southeast of Anatolia (Çelekli and Kapı, 2019;Çelekli and Arslanargun, 2019;Çelekli and Bilgi, 2019). Results indicated that TIT is an accurate diatom index when compared with the other diatom indices used to assess the ecological status of lotic ecosystems because of ecoregional environmental factors on the trophic weight of diatom taxa in Turkey (Lobo et al, 2004;Çelekli and Kapı, 2019).…”
Section: Trophic Index Turkeymentioning
confidence: 99%